Is China entering a high food price era?: A summary of CAER-IFPRI 2011 Annual International Conference - Nuetah, J. Alexander; Xiao, Yitian; Guo, Pei (Emerald Publishing Limited, 2012)
The purpose of this paper is to provide readers with the main findings and conclusions of papers presented at the 2011 CAER‐IFPRI International Conference held under the theme “Is China entering a high food price era?”The authors conduct a desk review of papers presented at the conference and provide a brief summary of the analytical tools, and main findings and conclusions of each presentation.These reviews show that, while there seems to be an increase in the prices of agricultural commodities on the Chinese market, in real terms, these rises fall far below the increases in the prices of industrial commodities. Thus, expert views remain divided on whether China is entering an era of high food price.The discussions initiated by the conference theme aroused researchers' curiosities for further studies into understanding the current level of food prices in China.